MODEL OF PROFESSIONAL COMPETENCE DEVELOPMENT OF TEACHERS OF TECHNICAL COLLEGES (Innovative professional education, 2024)
The article substantiates the definition of "professional competence of a technical college teacher", defines the structure of the phenomenon, characterizes the main types of professional competence of these pedagogical workers. The means of expert evaluation established that the most important are the educational, communicative, informational and digital, subject, methodical and educational competences of the teacher. A structural-content model consisting of four interdependent blocks is proposed and is an ideal representation of the development of professional competence of teachers of technical colleges.
Keywords: professional competence, technical college teacher, model, expert assessment, importance of types of professional competence